2000
DOI: 10.2460/ajvr.2000.61.1140
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic findings and association of Mycobacterium bovis infection with the bovine NRAMP1 gene in cattle from herds with naturally occurring tuberculosis

Abstract: The NRAMP1 gene does not determine resistance and susceptibility to infection with M bovis in cattle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
37
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 17 publications
(25 reference statements)
6
37
1
Order By: Relevance
“…The white doves had a lower prevalence of infection, fewer infected organs affected and a different pattern of inflammation as compared with the coloured doves. These data are consistent with epidemiological and genetic studies showing immune response polymorphism to mycobacterial infections in humans and other mammals (Bellamy, 2005;Dorman et al, 2004;Barthel et al, 2000;Pan et al, 2005;Di Pietrantonio & Schurr, 2005) and in different strains of chickens (Hu et al, 1997;Bacon et al, 2000). Specific genes that have been associated with differing immune responses to mycobacterial infections include those that code for the major histocompatability receptors, cytokines, T-cell receptors, immunoglobulins and NRAMP1 (Zekarias et al, 2002).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The white doves had a lower prevalence of infection, fewer infected organs affected and a different pattern of inflammation as compared with the coloured doves. These data are consistent with epidemiological and genetic studies showing immune response polymorphism to mycobacterial infections in humans and other mammals (Bellamy, 2005;Dorman et al, 2004;Barthel et al, 2000;Pan et al, 2005;Di Pietrantonio & Schurr, 2005) and in different strains of chickens (Hu et al, 1997;Bacon et al, 2000). Specific genes that have been associated with differing immune responses to mycobacterial infections include those that code for the major histocompatability receptors, cytokines, T-cell receptors, immunoglobulins and NRAMP1 (Zekarias et al, 2002).…”
Section: Discussionsupporting
confidence: 74%
“…Both environmental and genetic factors and their interaction influence susceptibility to tuberculosis in humans (Casanova & Abel, 2002;Schurr, 2007), in laboratory animals such as rabbits and mice, and in domestic mammals (Barthel et al, 2000;Phillips et al, 2002;Di Pietrantonio & Schurr, 2005;Dannemberg, 2006). For example, in humans infected with M. tuberculosis, less than 10% of infections progress to clinical disease (Cole et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The fragment described by Hořín et al (1999) was amplified using the primers and PCR conditions described by the same author. The (GT) n microsatellite of Adams and Templeton (1998) was analyzed using the primers and PCR conditions described by Barthel et al (2000). The SNP were genotyped using SNPlex technology by Applied Biosystems.…”
Section: Genetic Association Studymentioning
confidence: 99%
“…Indeed, Barthel and colleagues reported that polymorphic alleles in the 3'UTR (GT)n microsatellite of the SLC11A1 gene do not affect resistance or susceptibility to infection by M. bovis in cattle [24]. Importantly, the susceptible phenotype is due to a nucleotide substitution that results in an amino acid change, rather than polymorphisms in the 3'UTR (GT)n microsatellite sequences.…”
Section: Discussionmentioning
confidence: 99%